Alternative media for a populist audience? Exploring political and media use predictors of exposure to Breitbart, Sputnik, and Co. - Müller, P; Schulz, A (Taylor and Francis, 2019)
Alongside the recent rise of political populism, a new type of alternative media has established in past years that allegedly contribute to the distribution of the populist narrative. Using a large-scale quota survey of German Internet users (n = 1346) we investigate political and media use predictors of exposure to alternative media with an affinity to populism (AMP). Results reveal substantial differences between occasional and frequent AMP users. While both groups heavily use Twitter and Facebook for political information, occasional AMP users exhibit hardly any specific political convictions (except that they feel less personally deprived than non-users). Contrary to that, frequent AMP exposure is related to higher personal relative deprivation, stronger populist attitudes and a higher likelihood to vote for the right-wing populist party AfD. Against this background, frequent AMP use can be interpreted as partisan selective exposure whereas occasional AMP exposure might result from incidental contact via social media platforms. These findings are discussed regarding the role of alternative and social media in the recent populism wave.